Efektivitas Konten IShowSpeed Dalam Mempromosikan Budaya Indonesia Melalui Media Sosial Facebook - Andina Mustika Ayu; Alif Albiansyah; Sarah Shabirah (Jurnal Public Relations (J-PR), 2026)
Cultural promotion is an important part of public diplomacy in the digital age, particularly through the role of non-state actors such as social media influencers. This study aims to determine the impact of IShowSpeed’s content effectiveness in promoting Indonesian culture through Facebook on audience interest. Facebook was chosen because it is one of the platforms IShowSpeed uses to share content from his visits to Indonesia, thereby reaching a global audience. This study employs a quantitative approach using a survey of 100 respondents who are active followers of the IShowSpeed Facebook account. The 4C framework (Context, Communication, Collaboration, and Connection) is used as an indicator of content effectiveness, while Attention, Interest, and Desire serve as indicators of audience interest. The results show a Pearson correlation coefficient of 0.739, a coefficient of determination of 54.5%, and a calculated t-value of 10.844, which is greater than the critical t-value of 1.661. These findings indicate that the effectiveness of IShowSpeed’s content on Facebook has a significant impact on audience interest in Indonesian culture and supports the use of social media as a tool for international cultural diplomacy.